The impact of comorbidity upon determinants of outcome in patients with lung cancer. Issue 2 (February 2015) - Grose, Derek; Morrison, David S.; Devereux, Graham; Jones, Richard; Sharma, Dave; Selby, Colin; Docherty, Kirsty; McIntosh, David; Nicolson, Marianne; McMillan, Donald C.; Milroy, Robert; Scottish Lung Cancer Forum
Highlights Which combination of factors has the greatest impact on lung cancer survival? Survival appears to be determined by different factors which depend upon the stage of the cancer. This paper shows the importance of comorbidity particularly in early lung cancer survival.